2005
DOI: 10.1080/01443610500105993
|View full text |Cite
|
Sign up to set email alerts
|

What happens to women with chronic pelvic pain after a negative [normal] laparoscopy?

Abstract: Chronic pelvic pain remains unexplained in one third of women who have negative [normal] findings at diagnostic laparoscopy. This paper investigates the history of chronic pelvic pain after a negative laparoscopy and to assess the effect of negative laparoscopy on self perceived quality of life. The results of this study show that chronic pelvic pain persists in the majority of women who had negative laparoscopy in the medium to long term. It also shows that laparoscopy is beneficial in such group of women whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
1
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 2 publications
0
26
1
1
Order By: Relevance
“…This is in contrast to a recent study, which suggested that women with normal laparoscopy result had slightly improved quality of life in the medium to long term [10]. There are arguments for and against a diagnosis affecting CPP and quality of life.…”
Section: Laparoscopy Results and Follow-up Appointmentscontrasting
confidence: 90%
“…This is in contrast to a recent study, which suggested that women with normal laparoscopy result had slightly improved quality of life in the medium to long term [10]. There are arguments for and against a diagnosis affecting CPP and quality of life.…”
Section: Laparoscopy Results and Follow-up Appointmentscontrasting
confidence: 90%
“…Two groups reported that the laparoscopy helped patients cope with their symptoms, supporting the notion that a psychological element is involved in pelvic pain in the absence of pathology [7,24]. They explained that the pain improvements after laparoscopy were predicted by patientsÕ beliefs about the pain and a change in each patientÕs evaluation of the seriousness of her condition [24]. They thus concluded that diagnostic laparoscopy can have beneficial effects in women with chronic pelvic pain, and these effects appear to be the result of psychological mechanisms [7].…”
Section: Discussionmentioning
confidence: 73%
“…Investigators have evaluated the effects of diagnostic laparoscopy on women with chronic pelvic pain to explore possible psychological mechanisms. Two groups reported that the laparoscopy helped patients cope with their symptoms, supporting the notion that a psychological element is involved in pelvic pain in the absence of pathology [7,24]. They explained that the pain improvements after laparoscopy were predicted by patientsÕ beliefs about the pain and a change in each patientÕs evaluation of the seriousness of her condition [24].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…One of the most challenging aspects of clinical care is to determine the pain is either visceral, myofascial, or both. This challenge to the pelvic examination may be the reason for the recognized high rates of "negative" laparoscopies and high rates of repeated laparoscopies [71]. There are many anecdotal cases, and one reports that some women have had many laparoscopies for the excision of endometriosis [72].…”
Section: Multidisciplinary Carementioning
confidence: 99%